1996
DOI: 10.1136/bmj.313.7050.137
|View full text |Cite
|
Sign up to set email alerts
|

Sex related differences in short and long term prognosis after acute myocardial infarction: 10 year follow up of 3073 patients in database of first Danish verapamil infarction trial

Abstract: Objective-To re-examine the prevailing hypothesis that women fare worse than men after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…The characteristics of a selection of the published papers that present sex-comparative follow-up of at least 6 months are presented in Table 2. The longest follow-up was 14 years [30]; ten other reports presented a follow-up of 5 years or longer [12,29,30,33,[35][36][37][38]41,42]. Considering the average age at onset of AMI, a follow-up longer than 15 years would probably produce similar mortality rates in both sexes.…”
Section: Long-term Mortalitymentioning
confidence: 94%
See 1 more Smart Citation
“…The characteristics of a selection of the published papers that present sex-comparative follow-up of at least 6 months are presented in Table 2. The longest follow-up was 14 years [30]; ten other reports presented a follow-up of 5 years or longer [12,29,30,33,[35][36][37][38]41,42]. Considering the average age at onset of AMI, a follow-up longer than 15 years would probably produce similar mortality rates in both sexes.…”
Section: Long-term Mortalitymentioning
confidence: 94%
“…Mechanisms which may be implicated in this excess risk have not been established conclusively. The long-term fate of women is similar to that of men when survivors of AMI are considered [31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This gender gap was associated with strong gender differences in the provision of PCI during the index admission. We explored the possibility of gender disparities in the provision of health care for acute myocardial infarction patients but could not ascertain from the database whether such differences in revascularization could be explained by variation in eligibility, exclusion criteria, or patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, findings from large database studies [2][3][4][5][6][7][8][9][10][11] have indicated that women with acute myocardial infarction tend to undergo less aggressive hospital management than men. However, the relation of lower rates of revascularization is debated: Some studies have found that the excess mortality in women was explained by older age and higher baseline risk [12][13][14][15][16][17] or that it was restricted to a subgroup of female patients, whereas others have suggested that undertreatment in women had no effect on early mortality from acute myocardial infarction. 18,19 …”
mentioning
confidence: 99%
“…Increased mortality rates within 1 month after diagnosis is reported in young but not in older females (> 65 years) (Abildstrom et al, 2003;Chen et al, 1999;Rosengren et al, 2001). Others report no gender difference (Galatius-Jensen et al, 1996) or increased short-term mortality among males (MacIntyre et al, 2001). Although results are contradictory, most studies among older persons indicate worse survival among males on the long term (Kober et al, 1996;Vaccarino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%